Top Answer

We use the property of square roots that says the square root of (ab)=square root (a) multiplied by square root of b So square root (4x)=square root (4) mutiplies by square root of x =2(square root (x)) 2sqrt(x)

🙏

1🤨

4😮

4😂

1Loading...

4x to the sixth can be expanded to (4x * 4x * 4x)(4x * 4x * 4x) or (4x to the third)(4x to the third) the square root of the above would be 4x to the third

square root of 4x is 2 times square root of x, so answer is square root of x times 3 since it is 2 square roots of x plus one of them

If you square an expression and then take the square root, the squaring and the square root cancel one another, EXCEPT that the sign will be positive. Thus, if you square 16x, and then take the square root, the answer can be 16x or -16x, depending on whether "x" is positive or negative. Or if you only square x, and then take the square root of the entire expression, it would be 4x or -4x (once again, depending on whether "x" is positive or negative).

The square root of 4x^2 is solved by first doing the square root of 4. This is plus or minus two - because -2 x -2=4. The square root of x^2 is x. So the answers are 2x or -2x. If your question was (4x)^2, then the answer would be 4x.

If you mean: 4*square root of x2 then it is 4x

4x-8x = -4x √-4x stands. However, x could not possibly be a positive number, because: (Negative) X (Positive) = (Negative) The square root of a negative number is undefined-so... (√-4x) + 9 Is your answer.

No. The square root of 16 is.... 4 (4x4=16) and (-4x-4=16)

4x(21/2) Spoken: 4 times the quantity square root of two. Decimal: about 5.6569.

√(10x) * √(8x) = √(80x²)√(80x²) = √(16x²) * √(5) = 4x*√(5)■

(√4x^2)(√36x)=2x(6√x)=12x√x

No.

It is +/- 2x / sqrt(3y).

a square root is a number that when multiplied by itself gives a particular answer. 4x?=16 4x "the square root of 16"=16..we choose 16 because its square is 4 and when multiplied by itself gives us the final answer 16.

(4x - 5i)(4x + 5i)x = 1.25i, -1.25iwhere i is the square root of negative one.

y=(8x).5 + (4x).5 = (2+2sqrt(2))x.5 y'=(1 + sqrt(2))/sqrt(x)

root x=x^(1/2) and 4x =4 x^1 you add the exponents then integrate as usual. The answer you should get is 4.

perimeter of a square is 4x square that term (4x)(4x)and it gives you 16x2

13

Yes and x = 2+square root of 6 or x = 2-square root of 6

4x-x^2 \ 2-square root 2 multiply 2+squre root x\ 2+squreroot x = 4x-x^2 (2+squre root x) \ 4_x = x(4-x) (2+squre root x) \ 4-x we will cancel the (4-x) so it will be x(2+squre root x) = (0) (2+squre root 0) =0

There is nothing to solve because there is no = sign.

The square root of the left hand side is 2*(x - 1).The square root of the right hand side is 2*sqrt(14)

sqrt(10x)*sqrt(8x) = sqrt(80x2) = sqrt(16x2*5) = sqrt(16x2)*sqrt(5) = 4x*sqrt(5)

Using the quadratic equation formula the values of x are: x = -2 - the square root of 5 and also x = -2 + the square root of 5

x2 + 4x = 41